Meanings of Foundational Virtue in Islamic Mystical Ethics: A Case Study of Honesty - Seyed Ahmad Fazeli (Religious Inquiries, 2019)
In mystical ethics, some virtues have a foundational role in relation to other virtues; that is, other virtues are in some ways dependent on, conditional to, or rooted in them. This is a gradational concept, and therefore one can speak of foundational and more foundational among foundational virtues in mysticism. Honesty is the most foundational virtue in mystical ethics, and other virtues are in some way dependent on it. Studying mystical ethics sources, we find six types or six meanings of foundational, all of which apply to honesty: origin, prerequisite, overlapping, companion, companion of perfection, and standard. This article explains and describes these six meanings and their application to honesty in mystical sources.